Investigating the effects of accent on visual speech - Irwin, Amy (2008)
Speechreading is a complex skill affected by both the observer's method of extracting visual speech information and talker-specific variation in speech production. This thesis focuses upon accent, a factor that can influence both an observer's viewing strategy and talker speechreadability. Auditory research demonstrates that an unfamiliar accent reduces speech intelligibility. The primary aim here was to determine whether accent type, familiarity or variation would alter visual speech intelligibility with consequential effects upon speechreading performance. Experiments 1 and 2 considered visual discrimination of native and non-native accented speech and the influence of non-native accent upon speechreading performance. Results indicated that observers were able to utilise visual cues for discrimination and were significantly poorer at speechreading a non-native accent. Experiments 3, 4 and 5 examined the influence of regional accent on speechreading performance. Results indicated that visual speech performance was significantly worse for Glaswegian-accented talkers than for talkers with a Nottingham accent. However, no clear advantage for accent familiarity was found. Experiment 6 examined the influence of accent type and talker variability upon speechreading performance. Accent type was consistently the dominant influence upon speechreading performance, above familiarity and variation. Experiments 7, 8, 9 and 10 examined the influence of exposure, context and repetition upon the effects of a Glaswegian accent. Here, the effect of the Glaswegian accent on talker speechreadability was reduced by context and repetition, but not removed entirely.